The Good Governance Indicators of the Millennium Challenge Account: How many dimensions are really being measured - Martin Knoll; Petra Zloczysti (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
This paper assesses the validity of the perception-based governance indicators used by the US Millennium Challenge Account (MCA) for aid allocation decisions. By conducting Explanatory and Confirmatory Factor Analysis of data from 1996 to 2009, we find that although the MCA purports to measure seven distinct dimensions of governance, only two discrete underlying dimensions, the 'participatory dimension of governance' and the 'overall quality of governance' can be identified. Our results also show that some of the doubts that have been raised concerning the validity of perception-based governance indicators are less warranted when the indicators are applied exclusively to developing countries.
Keywords: C38; F35; O10; O51; 330; Aid Allocation; Governance Indicators; Factor Analysis; MCA